Determination of the activity concentration of 226Ra, 232Th, 40K and the concentration of 222Rn in soil samples of the Campos Gerais region (Paraná) (Brazilian Journal of Radiation Sciences, 2021)
In the Campos Gerais region of Paraná there are few literature that evaluate the concentrations of natural radioactivity. Thus, the aim of the present work was to determine activity concentrations of 226Ra, 232Th, 40K and 222Rn concentration in soil samples from Telêmaco Borba, Tibagi, Curiúva, Ventania, Lageado Bonito and Ortigueira. The soil samples, with about 2 kg, were collected on the surface at points near the river bed, making sure that the soil is not under the agriculture influence. Gamma-ray spectrometry analyzes were performed with a NaI(Tl) scintillation detector, with dimensions of 76 mm in diameter, 152 mm in height and 8 cm of lead shield. The 222Rn concentration determinations were performed by means of the sealed can technique, using as track detector a polycarbonate of domestic manufacture. The results obtained for the activity concentration varied from
Keywords: soil; radon; gamma ray